From Sunshine to Midnight Rain: The Dynamics of Abusive Romantic Relationships among Women Victims - Sayidina, Miastika Nur; Nurhadi, Nurhadi (LPPM Institut Pendidikan Nusantara Global, 2025)
Dating violence is a form of gender-based violence that frequently occurs within romantic relationships. This study aims to examine the understanding of dating violence from the victims’ perspectives. It also seeks to identify the types of violence experienced and the responses of victims in the Surakarta region and surrounding areas. This research adopts a qualitative design with a phenomenological approach. Data were collected through semi-structured interviews. The findings indicate that victims possess a relatively good understanding of dating violence. However, this understanding does not necessarily empower them to break free from the cycle of violence. The violence experienced by victims is categorized into two types: non-physical and physical violence. Non-physical violence includes possessiveness, restriction of freedom, verbal abuse, psychological abuse, and economic abuse. Physical violence consists of physical assault and sexual violence. Not all victims reported experiencing extreme forms of abuse, such as physical or sexual violence. However, all participants experienced some form of non-physical violence. Several factors were identified as contributing to victims’ decisions to remain in abusive relationships, including emotional attachment (love), dependency, and family-related reasons.